Groupwork and Feedback: Does the introduction of group average feedback impact on student opinion of groupwork in a mathematics class? - Jordan, L (2017)
From a mathematics teacher perspective, group work is an invaluable learning tool which allows for discussion and sharing of ideas and methods with peers and friends. However students can appear not to share our affinity for group work, often complaining of unfair distribution of workload and competition within groups. To investigate the impact of individual accountability combined with group reward incentive (Boaler, 2008; Johnson and Johnson, 2008) on student opinion on group work within the mathematics classroom, an intervention was implemented in which students were placed in heterogeneous ability groups for a term with individual assessment results contributing to a group average result at the end of the term. This intervention utilised the STAD (Slavin, 1983;2015) method of collaborative teaching and learning by utilising group average feedback to improve and encourage cooperative learning with groups in maths lessons. No group work teaching strategies such as Jigsaw or pre-coaching were utilised in the period in which students were working in these groups and students were not encouraged to learn or interact in specific ways within their groups to limit alternative influences on student opinion. The intervention was implemented with two classes and student opinion was evaluated using a sequence of questionnaires. Interviews were also utilised to further analyse and evaluate student opinion on group work. The findings suggested this intervention had an impact on student opinion but to ensure a positive impact additional teaching and learning strategies should also be undertaken.